Study the Effect of Formulation Variables on Preparation of Nisoldipine Loaded Nano Bilosomes - Al-Edhari, Ghada Hamid; Al Gawhari, Fatima Jalal (Iraqi Journal of Pharmaceutical Sciences, 2023)
Nisoldipine (NSD) is a dihydropyridine class of calcium channel blockers used for hypertension treatment, it belongs to class II BCS (low solubility with high permeability), its absolute bioavailability is only 5% due to presystemic metabolism in the gut wall. It is also a substrate for a CYP3A and P-gp.Bilosomes are lipid bilayer vesicles incorporating bile salts in their walls to prevent degredation by GIT bile salts.The aim of this study is to prepare nisoldipine bilosomes as vesicular carrier and assess the effect of different formulation variables such as type of surfactant, amount of cholesterol, surfactant and sonication time on particle size, entrapment efficiency and poly dispersity index of the prepared bilosomes.The prepared bilosomes were prepared by thin film hydration method and they were optimized using different types of non-ionic surfactants span20, 40 and 60 along with different amount of cholesterol and different sonication time.The prepared formulas have particle size between 138.3 -392.4 nm, polydispersity index 0.12- 0.4 and entrapment efficiency equal to 48-82%.Results showed that increasing cholesterol amount lead to increase entrapment with increase particle size further increase leads to decrease entrapment with further increase in particle size. While increase amount of surfactant (span 60) give higher entrapment of drug with decrease particle size. Span 60 give the best entrapment efficiency and increasing sonication time is associated with decrease in particle size and entrapment efficiency.